Generation X: implications for faculty recruitment and development in academic health centers - Bickel, Janet; Brown, Ann J (Academic medicine : journal of the Association of American Medical Colleges, 2005)
Differences and tensions between the Baby Boom generation (born 1945-1962) and Generation X (born 1963-1981) have profound implications for the future of academic medicine. By and large, department heads and senior faculty are Boomers; today's residents and junior faculty are Generation X'ers. Looking at these issues in terms of the generations involved offers insights into a number of faculty development challenges, including inadequate and inexpert mentoring, work-life conflicts, and low faculty morale. These insights suggest strategies for strengthening academic medicine's recruitment and retention of Generation X into faculty and leadership roles. These strategies include (1) improving career and academic advising by specific attention to mentoring "across differences"--for instance, broaching the subject of formative differences in background during the initial interaction; adopting a style that incorporates information-sharing with engagement in problem solving; offering frequent, frank feedback; and refraining from comparing today to the glories of yesterday; to support such improvements, medical schools should recognize and evaluate mentoring as a core academic responsibility; (2) retaining both valued women and men in academic careers by having departments add temporal flexibility and create and legitimize less-than-full-time appointments; and (3) providing trainees and junior faculty with ready access to educational sessions designed to turn their "intellectual capital" into "academic career capital."Given the trends discussed in this article, such supports and adaptations are indicated to assure that academic health centers maintain traditions of excellence.